EVERYDAY LIFE OF STUDENTS AND WORKING YOUTH IN THE REAR DURING THE GREAT PATRIOTIC WAR (ON THE EXAMPLE OF KABARDINO-BALKARIA - Tetuev, Alim Inzrelovic (History, Archeology and Ethnography of the Caucasus, 2023)
For the first time, on the basis of new archival documents and other sources, the features of the everyday life of students of institutions of higher and secondary vocational education and working youth in wartime conditions are studied using the example of Kabardino-Balkaria. The influence on the daily life of students of the restructuring of the work of educational institutions of vocational education in accordance with the requirements of wartime is revealed. The problems of educational and labor activity of students are revealed. The activities of working youth in helping the front are summarized: participation in partisan detachments, underground sabotage work during the occupation of the republic, raising funds for the National Defense Fund, warm clothes and gifts for the soldiers of the Red Army, providing patronage assistance to military families and orphans. The contribution of urban and rural youth to the development of the economy of the republic in the interests of the front and rear has been studied. Various forms of increasing labor activity and issues of youth participation in the restoration and development of the national economy of the region are considered. It is concluded that the restructuring of the work of educational institutions of vocational education in the interests of the front and rear has significantly affected the daily life of students. Military and physical training, patriotic and labor education allowed them to assist the front and rear and overcome the difficulties of wartime. Despite the limited material and living conditions, the working youth provided significant assistance to the front and socially unprotected groups of the population. In the everyday life of urban and rural youth, work was the main thing. The youth of the home front, showing patriotism and a desire to bring the Victory closer, made a significant contribution to the economy of the region and the country.